Norops biporcatus (Wiegmann, 1834). Color change during foraging - Esquivel, Carolina (2017)
Reptiles use body colors for many purposes: camouflage, warning predators, mate choice, and thermoregulation, among others (Cooper and Greenberg, 1992). The body color of anoles results from a combination of three pigments (pteridines, carotenoids, and drosopterines), as well as from structural coloration (Macedonia et al., 2000). These lizards are known for their ability to change color by expanding or contracting melanin in their skin cells (Horowitz, 1958). One of the best-studied cases of color change in anoline lizards involves Anolis carolinensis, in which the evidence presented shows that this species changes color to match its background (Hadley, 1929; Kleinholz, 1938; Dores et al., 1987). Nonetheless, Jenssen et al. (1995) found the opposite in that lizards mismatched their background more than would be expected by chance. Other studies also have shown that A. carolinensis changes its skin color during sexual interactions, territorial defense, stress, predation, and according to the temperature and light conditions (Greenberg et al., 1984; Cooper and Greenberg, 1992; Jenssen et al., 1995).